Sejarah wilayah perbatasan Miangas-Filipina, 1928-2010 : dua nama satu juragan - Ulaen, Alex John.; Wulandari, Triana; Tangkilisan, Yuda B.; Djaenuderadjat, Endjat (Depok : Gramata Pub., 2012)
History of Miangas Island as a border crossing area between Indonesia and the Philippines.
Kepustakaan : p. 215-224.
Keywords: Miangas Island (Indonesia) -- History; Indonesia -- Boundaries -- Philippines; Philippines -- Boundaries -- Indonesia